Tumour Recurrence, Depth of Invasion, and Temple Location as Independent Prognostic Parameters of Lymph Node Metastases of Head and Neck Cutaneous Squamous Cell Carcinomas - Horakova, Zuzana; Starek, Ivo; Zapletalova, Jana; Salzman, Richard (International journal of clinical practice, 2024)
The excellent survival rate of cutaneous squamous cell carcinoma (cSCC) exceeding 90% is reduced by the presence of nodal metastases by over 50%. We analysed various risk parameters of cSCC to predict the incidence of nodal metastases. A total of 118 patients with the head cSCC were included in a single-institution retrospective study covering the period from 2008 to 2020. Tumour recurrence, temple location, and tumour infiltration depth were found to be independent predictors of nodal metastases (increasing the probability of metastases by 8.0, 8.1, and 4.3 times, respectively). Furthermore, univariate analysis shows that the tumour size and T stage are significant factors increasing the risk of metastases. Several independent risk factors for the development of metastases in the head cSCC have been confirmed. These findings might help identify at-risk patients who require additional attention for adequate radical treatment and close follow-up. In contrast, elective treatment of lymph nodes is not recommended due to the low incidence of regional metastases.
Keywords: Neoplasm Staging; Neoplasm Recurrence, Local; prognóza; Prognosis; nádory kůže; Carcinoma, Squamous Cell; nádory hlavy a krku; lidé; retrospektivní studie; staging nádorů; Head and Neck Neoplasms; Skin Neoplasms; spinocelulární karcinom; Retrospective Studies; Lymphatic Metastasis; lymfatické metastázy; lokální recidiva nádoru; Humans